An indirect Raman spectroscopy method for the quantitative measurement of respirable crystalline silica collected on filters inside respiratory equipment. Issue 21 (21st May 2020) - Stacey, Peter; Clegg, Francis; Morton, Jackie; Sammon, Christopher
Abstract : A new Raman method for respirable crystalline silica that is capable of measuring concentrations below the limits of detection of current analytical methodology and worker exposures when wearing respirators. Abstract : This article describes the development of an analytical method to measure respirable crystalline silica (RCS) collected on filters by a miniature sampler placed behind respirators worn by workers to evaluate their 'true' exposure. Test samples were prepared by aerosolising a calibration powder (Quin B) and by pipetting aliquots from suspensions of bulk material (NIST 1878a and Quin B) onto filters. Samples of aerosolised RCS collected onto polyvinyl chloride PVC filters were ashed and their residue was suspended in isopropanol and filtered into a 10 mm diameter area onto silver filters. Samples were also collected by the Health and Safety Executive's (HSE) miniature sampler from within the facepiece of a respirator on a breathing manikin during a simulated work activity. Results obtained using Raman spectroscopy were compared with X-ray diffraction (XRD) measurements, which was used as a reference method and a linear relationship was obtained. Raman has similar estimates of uncertainty when compared with the XRD methods over the measurement range from 5 to 50 μg and obtained the lowest limit of detection (LOD) of 0.26 μg when compared with XRD and Fourier Transform Infrared FTIR methods. A significant intercept and slope coefficient greatly influenced the higher LOD for indirect XRD method. The level of precision and low LOD for Raman spectroscopy will potentially enable workplace measurements at lower concentrations below the Workplace Exposure Limit (WEL) than are achieved using current analytical instrumentation. Different inward leakage ratio (ILR) measurement approaches were compared using six aerosolised sandstone dust tests. For the three highest inward leakage ratios the Portacount® obtained higher values than the RCS mass or the miniWRAS ratios, the latter of which reporting both particle number and quartz mass concentration. However, these limited ILR data were insufficient to establish statistical correlations between the measurement methods.